2021
DOI: 10.1128/mbio.02608-21
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Impacts Intracellular Accumulation Only in Actively Growing Bacterial Cells

Abstract: This study shows that efflux is important for maintaining low intracellular accumulation only in actively growing cells and that envelope permeability is the predominant factor in stationary-phase cells. This conclusion means that (i) antibiotics with intracellular targets may be less effective in complex infections with nongrowing or slow-growing bacteria, where intracellular accumulation may be low; (ii) efflux inhibitors may be successful in potentiating the activity of existing antibiotics, but potentially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…The resulting parameters suggest early rapid accumulation of the substrate followed by a decrease in cell permeability. This compares favourably against more recent experimental data that demonstrate that changes in substrate accumulation in later growth are dominated by changes in permeability rather than efflux [43].…”
Section: Quantifying Effluxsupporting
confidence: 75%
“…The resulting parameters suggest early rapid accumulation of the substrate followed by a decrease in cell permeability. This compares favourably against more recent experimental data that demonstrate that changes in substrate accumulation in later growth are dominated by changes in permeability rather than efflux [43].…”
Section: Quantifying Effluxsupporting
confidence: 75%
“…Supporting this, deletion of dskA in E. coli resulted in a significant increase in acriflavine susceptibility (), however previous work found no significant difference in efflux activity following deletion of rpoS in S. Typhimurium [39]. These genes may affect efflux regulation through marR , whose expression has been reported to increase (resulting in repression of marA ) following deletion of either dksA [40] or rpoS [41].…”
Section: Resultsmentioning
confidence: 94%
“…In the study of Whittle et al (2021) , the authors showed that there was no significant difference in EtBr accumulation when measuring it in single cells, at different growth phases. Only one case was different, when efflux deficient strains were used.…”
Section: Discussionmentioning
confidence: 99%